An Exploitation of Satire in Ngozi Chuma-Udeh’s Teachers on Strike - Segun, Aminu; Abiodun, Adetoro (International Journal For Research In Educational Studies, 2016)
Literature can be seen as the mirror of life, which shows the action of man in the society. To mirror this society, writers usually rise to the occasion using the medium of arts to express people‟s mind. It is common knowledge that the problems associated with democratization in Nigeria have left a profound mark in literary circle as there have been gradual shift from military misrule to that of political and social diagnosis. The satirical portrayal of the Nigeria political class, the meddlesomeness of the working class and the all pervading cynicism in the polity are all that is looked on by writers. As a result of the spirit of patriotism and nationalism, the source and inspiration of their work came, as they were victims of harsh economic situation and corrupt environment. To pass across their message, these writers explored a unique style of writing through which they ridicule and make caricature of their society. This style of writing is said to be a social criticism whereby the actions and thoughts of man are criticized in a positive way. This unique style is known as satire. This work takes a look at the exploitation of satire in Ngozi Chuma-Udeh‟s Teachers on Strike.